2017
DOI: 10.1007/s10712-017-9433-3
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cloud Feedbacks from Cloud-Controlling Factors: A Review

Abstract: The response to warming of tropical low-level clouds including both marine stratocumulus and trade cumulus is a major source of uncertainty in projections of future climate. Climate model simulations of the response vary widely, reflecting the difficulty the models have in simulating these clouds. These inadequacies have led to alternative approaches to predict low-cloud feedbacks. Here, we review an observational approach that relies on the assumption that observed relationships between low clouds and the ''c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
176
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(216 citation statements)
references
References 73 publications
15
176
1
Order By: Relevance
“…Our observational analysis when considered together with these modeling results implies stronger latent warming and possibly higher climate sensitivity than current estimates for many models because the SST‐LCC feedback of current models is too weak. SST‐LCC feedback being too weak in many models suggests that a higher equilibrium climate sensitivity might be more realistic (see Klein et al, 2017, and references therein). Indeed, we find that models capturing better the SST‐LCC coupling, as measured by the spatial correlation, have higher values of equilibrium climate sensitivity (Figure S7), which may be a result of both stronger overall positive cloud feedback and stronger latent warming.…”
Section: Summary and Discussion: Relevance To Future Warmingmentioning
confidence: 99%
“…Our observational analysis when considered together with these modeling results implies stronger latent warming and possibly higher climate sensitivity than current estimates for many models because the SST‐LCC feedback of current models is too weak. SST‐LCC feedback being too weak in many models suggests that a higher equilibrium climate sensitivity might be more realistic (see Klein et al, 2017, and references therein). Indeed, we find that models capturing better the SST‐LCC coupling, as measured by the spatial correlation, have higher values of equilibrium climate sensitivity (Figure S7), which may be a result of both stronger overall positive cloud feedback and stronger latent warming.…”
Section: Summary and Discussion: Relevance To Future Warmingmentioning
confidence: 99%
“…Previous studies have indicated that climatologicalmean distribution of LCF and its seasonality are well explained by lower-tropospheric stability, whose enhancement acts to increase LCF (e.g., Klein and Hartmann 1993;Wood and Bretherton 2006;Koshiro and Shiotani 2014). Climatological-mean distributions of EIS defined in (1) are thus shown in Figs.…”
Section: B Meteorological Parametersmentioning
confidence: 95%
“…For example, stratocumulus clouds prevail over the eastern portion of each of the subtropical ocean basins (e.g., Klein and Hartmann 1993;Wood 2012), which is located east of a surface subtropical high that accompanies persistent midtropospheric subsidence and equatorward surface winds (e.g., Nakamura 2005, 2010). The equatorward winds induce coastal upwelling and upper-ocean mixing in addition to surface evaporation, acting to maintain relatively low sea surface temperature (SST).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations